Bridging Teks and Minds: The Impact of Text-Based Learning on Student’s Reading Engagement: Penelitian - Uswatun Hasanah; Melani Indriyani Persidikin; Ardiana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to improve students’ reading comprehension through the use of the Text-Based Learning (TBL) model in class IX B of SMPN 1 Galesong Selatan. Conducted as Classroom Action Research across two cycles, the study involved planning, action, observation, and reflection. Data were collected through a pre-test, post-test Cycle I, post-test Cycle II, observation sheets, and field notes. The results showed a consistent increase in students achieving the minimum mastery criterion (KKM 75). In the pre-test, only 6 students (25%) reached mastery. This improved to 12 students (50%) in Cycle I and further increased to 17 students (70.8%) in Cycle II, meeting the success indicator of the study. The improvement occurred because TBL provided structured guidance through topic introduction, teacher modeling, collaborative activities, and independent practice. These stages helped students understand text organization, identify the main idea, interpret detailed information, and comprehend vocabulary more effectively.